THE INFLUENCE OF JOB DESCRIPTION ON THE PERFORMANCE OF SECURITY DEPARTMENT EMPLOYEES - Kurniawan, Indra; David-Barrett, Tamas (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Security has a job description that will guide and direct so that the work becomes smooth and controlled according to the regulations set by the company. Research Purpose. The purpose of this study was to determine the effect of job descriptions on employee performance. Research Method. This study uses an explanatory quantitative research approach using a survey as a data collection tool that aims to determine how a variable affects other variables. The population in this study were all employees of the security department in a company with a total of 46 people. The sampling method uses a non-probability sampling method, namely saturated sampling because it takes samples from the entire total population, using a Likert scale, this research is a survey research where primary data is collected through distributing questionnaires, secondary data is collected from companies, and literature studies. The data analysis method used is the descriptive analysis method with a simple linear regression analysis technique and Crosstab as a tool to calculate whether there is a relationship or influence between Job description on employee performance. Findings. The results of simple linear regression analysis, it can be said that the dependent variable (Y) changes to the independent variable (X), but the remaining part is caused by other factors that are not included in the model or this study, including the variables of motivation and ability. Conclusion. The job description variable has a positive and significant effect on the performance of employees of the security department of the company.